Inflation Pressure Effect on Coefficient of Rolling Resistance of Two Wheel Camel Cart - Verma, Ajay Kumar; Singh, Pratap (Annals of Arid Zone, 2016)
Tyres of ten different sizes commonly used in two wheel camel carts in western Rajasthan were tested at different inflation pressures and payloads to find out the optimum values of inflation pressures. It was found that coefficient of rolling resistance (CEtR), decreased by about 8 to 19 % on sandy terrain and increased by about 7 to 12 %on tarmacadam road, by reducing the normal tested range of inflation pressure.